Advances in discourse analysis of translation and interpreting : linking linguistic approaches with socio-cultural interpretation - Wang, Binhua; Munday, Jeremy, 1960- (Routledge advances in translation studies, 2021)
This edited thematic collection features latest developments of discourse analysis in translation and interpreting studies. It investigates the process of how cultural and ideological intervention is conducted in translation and interpreting using a wide array of discourse analysis and systemic functional linguistic approaches and drawing on empirical data from the Chinese context. The book is divided into four main sections: 1) uncovering positioning and ideology in interpreting and translation, 2) linking linguistic approach with socio-cultural interpretation, 3) discourse analysis into news translation, and 4) analysis of multimodal and intersemiotic discourse in translation. The different approaches to discourse analysis provide a much-needed contribution to the field of translation and interpreting studies. This combination of discourse analysis and corpus analysis demonstrates the interconnectedness of this fields and offers a rich source of conceptual and methodological tools. This book will appeal to scholars and research students in translation and interpreting studies, cross-linguistic discourse analysis and Chinese studies.